2013
DOI: 10.1101/gad.210963.112
|View full text |Cite
|
Sign up to set email alerts
|

SFMBT1 functions with LSD1 to regulate expression of canonical histone genes and chromatin-related factors

Abstract: SFMBT1 (Scm [Sex comb on midleg] with four MBT [malignant brain tumor] domains 1) is a poorly characterized mammalian MBT domain-containing protein homologous to Drosophila SFMBT, a Polycomb group protein involved in epigenetic regulation of gene expression. Here, we show that SFMBT1 regulates transcription in somatic cells and during spermatogenesis through the formation of a stable complex with LSD1 and CoREST. When bound to its gene targets, SFMBT1 recruits its associated proteins and causes chromatin compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 67 publications
(98 reference statements)
6
80
0
Order By: Relevance
“…14,15 Moreover, expression of recombinant full-length SFMBT1 or its MBT domains in cell lines reduces chromatin accessibility to nuclease digestion. 23 As we will detail below, MBT domain proteins are found in several multisubunit protein complexes (see Table 1 for a list of MBT and CoREST complexes discussed in this review). They provide these complexes with a tool (the MBT domains) for binding to mono-and di-methylated nucleosomes and for establishing repressive chromatin structures, potentially by way of nucleosome compaction.…”
Section: -23mentioning
confidence: 99%
See 4 more Smart Citations
“…14,15 Moreover, expression of recombinant full-length SFMBT1 or its MBT domains in cell lines reduces chromatin accessibility to nuclease digestion. 23 As we will detail below, MBT domain proteins are found in several multisubunit protein complexes (see Table 1 for a list of MBT and CoREST complexes discussed in this review). They provide these complexes with a tool (the MBT domains) for binding to mono-and di-methylated nucleosomes and for establishing repressive chromatin structures, potentially by way of nucleosome compaction.…”
Section: -23mentioning
confidence: 99%
“…However, recent studies in human and Drosophila have identified novel assemblies that combine MBT and CoREST proteins [20][21][22][23] (Table 1). Human SFMBT1 was isolated in a complex with LSD1 and CoREST (SLC complex) and the remaining subunits of known CoREST complexes.…”
Section: Mbt and Corest Proteins In Common Complexesmentioning
confidence: 99%
See 3 more Smart Citations